Fractal Dimension of S&P CNX Nifty Stock Returns - GAYATHRI, Mahalingam; SELVAM, Murugesan; LINGARAJA, Kasilingam; VASANTH, Vinayagamoorthi; KARPAGAM, Venkatraman (Asian Journal of Empirical Research, 2013)
A fractal is a geometrical structure that is self-similar when scaled. By assessing the fractal dimension of asset returns, the retail investors with recent innovation in financial prediction and computational power, can exploit these prices. A branch of a tree is often used as an example in Fractal. The branch is similar to the whole tree and if we break a twig off the branch, the twig is similar to the branch. In a true, mathematical, fractal dimension, this scaling goes on forever but in all real systems, there is the largest and smallest scale which exhibit fractal behavior. The main aim of this study is to predict the prices in the stock market and thus give profitable opportunities to the investors and financial analysts. This paper examined the fractal dimension of returns of top five companies - ITC Limited, Reliance Industries Limited, Infosys Limited, ICICI Bank Limited and HDFC Limited, listed in the S&P CNX Nifty Index. The Rescaled Range (R/S) Analysis was used to detect the long-term memory. The analysis of results found that fractal dimension existed in the returns of stocks in the market.